MENINGKATKAN PEMAHAMAN TEKNIK SERVIS MELALUI PENGGUNAAN VIDIO TUTORIAL PADA EXTRAKURIKULER BADMINTON DI PB ELANG YOGYAKARTA - Chun Chun, Adelbertus; Kurniawan, Rafif Arkhab; Pamungkas, Bima Arya; Marta, Ilyas Hadi; Wirayuda, Angga; Komalasari, Mahilda Dea (WIDYA DIDAKTIKA - Jurnal Ilmiah Kependidikan, 2025)
This study aims to improve students’ understanding of basic badminton service techniques through the use of video tutorial media in the extracurricular program at PB Elang Yogyakarta. The research employed Classroom Action Research (CAR) conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. The subjects were 15 students, comprising 9 male and 6 female participants. Data were collected through observation and skill tests based on 10 assessed technical aspects. The results indicated a significant improvement from the pre-cycle to the second cycle. In the pre-cycle, most students did not meet the minimum competency criteria. By the end of the second cycle, 73% of students were categorized as “Good” and “Very Good,” with no students remaining in the “Poor” or “Very Poor” categories. These findings demonstrate that video tutorial media is effective in enhancing students’ comprehension and performance in badminton service techniques.